IMPLEMENTASI PENGAMANAN DATABASE MENGGUNAKAN MD5 - Khairil, Khairil; Ginta, Prama Wira (Jurnal Media Infotama, 2012)
Technology is a very important need in the current technological era, the development of computer technology is currently very important for the world of public services, industry, white collars, education, the world of commerce and engineering. For this reason, computers as data processors have an important role in terms of speed, reliability and caution in processing data so as to produce maximum information. To manage institutional data effectively, institutions that manage educational services must check quickly and precisely how they serve children in educational institutions. Modern data management is also an important condition for success. Manage and control the service process in learning so that goals can be realized in accordance with expectations. Seeing such problems and situations, the application and utilization of information technology (chosen by IT) solutions must be compatible, so that they can help an educational institution improve its performance, which leads to increased revenue and net income. To be able to improve performance.